Productive Alliances : Social Benefit of Oil Palm - Federación Nacional de Cultivadores de Palma de Aceite, Fedepalma (Federación Nacional de Cultivadores de Palma de Aceite, 2020)
Association and inclusive business models for rural areas, where the private sector plays a critical role in the development and formalization of the countryside.
Keywords: Palma de aceite; Alianzas; Modelo; Responsabilidad social; Asociaciones; Formalización; Empleo